Analisis Hukum Islam terhadap Ketidakmampuan Istri Memiliki Anak sebagai Alasan Perceraian dan Poligami - Badruzaman, Dudi (Tasfiyah : Journal of Islamic Law and Sharia Economics, 2026)
Marriage in Islam aims to form a family that is sakinah, mawaddah, wa rahmah and taking care of offspring as one of the important purposes of sharia. However, in the practice of domestic life, not all couples are blessed with children. The condition of a wife who cannot have children is often used as an excuse by the husband to divorce or polygamy. This study aims to analyze the views of Islamic law regarding the reasons why wives cannot have children in cases of divorce and polygamy. The research method used is qualitative research with a normative juridical approach and a type of literature research. Data sources are obtained from the Qur'an, Hadith, jurisprudence, Compilation of Islamic Law, laws and regulations, and relevant scientific literature. The data analysis technique was carried out in a descriptive analytical manner. The results of the study show that the wife's inability to have children is not an absolute reason that automatically justifies divorce, because in Islam divorce is the last resort after deliberative efforts and treatment efforts are carried out. In addition, the absence of children does not always come from the wife's side, but can also be caused by the husband factor. Polygamy in Islam is allowed with certain conditions, especially the existence of justice and the ability of the husband. Therefore, the reason for not having children cannot be used as a unilateral basis without considering the value of justice, responsibility, and welfare in the household. This research emphasizes that Islamic law views the issue of heredity in a proportional, humane manner, and based on the principle of justice.